Amazing screw-on head and other curious objects anniversary edition ebook - Mignola, Mike (The Amazing Screw-On Head., 2022)
Includes forty pages of new material by Mike Mignola!Emperor Zombie is trying to take over the world once again! The Amazing Screw-On Head has been enlisted by President Lincoln to stop the evil emperor, with the help of his faithful partner Mr. Groin and his trusty canine companion Mr. Dog. Screw-On Head will have to brave ancient tombs and defeat demons from a dimension inside a turnip—just one of the strange and mischievous tales in this beloved collection.This special edition of The Amazing Screw-On Head and Other Curious Objects celebrates the twentieth anniversary of the Eisner Award-winning collections original publication, and includes an additional forty pages of new material by Mike Mignola! Featuring colors by the great Dave Stewart.""The stories that make up the Screw-On Head collection are actually my favorite things I've done"" –Mike Mignola• The forty new pages include an unpublished story called Axorr which is 19 finished line art pages (plus a page of story notes, a concept sketch, and a promo piece), plus additional colored illustrations.